Sistem Kunci Pintu Berbasis IOT dengan RFID untuk Meningkatkan Kemudahan Akses Pada Lansia - Rosalina Wadjin; Mohammad Sidqon (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to design and implement an Internet of Things (IoT)-based door lock system using Radio Frequency Identification (RFID) technology to improve accessibility for elderly users. The background of this research is based on the physical and cognitive limitations experienced by elderly individuals, which often make it difficult to use conventional door locks. The method used includes hardware design involving RFID modules, microcontrollers, and integration with an IoT platform for remote monitoring and control. This system allows users to unlock the door using an RFID card without requiring a physical key and provides real-time access notifications. The testing results show that the system operates with high RFID reading accuracy and fast response time. In addition, the system is considered more practical and easier to use by elderly users compared to conventional locking systems. Therefore, the implementation of IoT and RFID technology in door lock systems can improve both security and accessibility for elderly users. This research is expected to provide an innovative solution to support the independence of elderly people in their living environments.